INTEGRASI KENDALI LENGAN ROBOT BERBASIS INVERSE KINEMATIC DAN ISYARAT SUARA - , TITO GARRY SURYA B ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Particularly the control of robot technology hardware to follow other technology areas with rapid development. Various kinds of actuators such as DC motors, servo motors, pneumatic, hydraulic has to be controlled by various methods of control. One of these methods is often called motion reverse or Inverse Kinematics. Using this method the algorithm becomes more difficult for the user but it gives more precise results because the motion of the system, such as a robot arm, the focus based on the requested endpoint. By using voice recognition application as a command input is then fed to the robot arm control system to assist in making the desired device, is expected to facilitate a person to do the job. The results of this study are expected in the form of a robotic arm that can help a person in terms of taking objects at specific coordinates. Motion control of a robotic arm using Inverse Kinematics are processed using the Arduino Uno controller and use voice commands as input. The level of accuracy of the coordinates of the robot arm high enough that the X accuracy 92.50 %, Y accuracy 94.76%, and Z accuracy 91.42%.